Terra brasilis, ex Corde: política, cultura e Estado nas octogenárias Raízes do Brasil - Diego Vinícius Vieira (2017)
The present dissertation has the main objective to explore the book Roots of Brazil (1936), by Sérgio Buarque de Holanda. We know, at 80 years of its publication, the essay continues to instigate several discussions in the brazilian political thought. Our contribution, therefore, begins in the years of formation and main intellectual dialogues of the author, to reach the vastness of his contributions in the History of Brazilian Culture and Brazilian State. Finally, we analyze the peculiar readings that appears in a new centenary, contrasting them with the positions of interpretation that we prefer to adopt.